ChemInform Abstract: Condensation of Vilsmeier Salts, Derived from Tetraalkylureas, with Amidoximes: A Novel Approach to Access N, N‐Dialkyl‐1, 2, 4‐oxadiazol‐5‐amines. Issue 14 (8th April 2014) - Su, Dongshan; Duan, Haifeng; Wei, Zhonglin; Cao, Jungang; Liang, Dapeng; Lin, Yingjie
Abstract The condensation of Vilsmeier salts and amidoximes proceeds under mild conditions to give oxadiazol derivatives.